Clinical outcomes of cataract surgery with implantation of extended depth of focus intraocular lenses - Tran, Nguyen Tra My; Duong, Anh Quan; Tran, Sy Thanh (Tạp chí Y Dược Huế, 2024)
Background: Cataract is a leading cause of blindness in Vietnam and worldwide. Phacoemulsification with extended depth of focus intraocular lenses helps patients achieve their desired vision in distance and intermediate vision, improve near vision, and minimize phenomena such as halos and glare. Objectives: To evaluate the clinical outcomes of cataract surgery with implantation of extended depth of focus intraocular lenses. Subjects and Methods: A prospective interventional clinical study was conducted on 57 eyes of 50 cataract patients who underwent phacoemulsification with implantation of the extended depth of focus intraocular lenses. Results: At 3 months after surgery, the uncorrected and corrected distance visual acuity (logMAR) were 0.07 ± 0.07 and 0.06 ± 0.06; The uncorrected and corrected intermediate visual acuity (logMAR) were 0.26 ± 0.12 and 0.25 ± 013; The uncorrected and corrected near visual acuity (logMAR) were 0.55 ± 0.20 and 0.54 ± 0.19; Most patients did not experience symptoms of halos and glare. Satisfaction rates were high, with 94.7% of patients reporting satisfaction or high satisfaction with the surgery. Conclusion: Phacoemulsification with extended depth of extended depth of focus intraocular lenses yields high efficacy in terms of visual acuity and patient satisfaction